The Urgency of Trademarks for Home Industry Processed Food Producers: Developments and Challenges - Riyanto, R Benny; Arifin, Ridwan; Karsinah, Karsinah; Fibrianti, Nurul; Al Farouq, Alamul Fikri (Universitas Negeri Semarang, 2023)
In the rapidly evolving landscape of the global food industry, home industry processed food producers play a crucial role in contributing to local economies and meeting the diverse culinary preferences of consumers. However, as these producers strive for recognition and market presence, the importance of trademarks cannot be overstated. This paper explores the urgency of trademarks for home industry processed food producers, shedding light on the myriad benefits and challenges associated with establishing and protecting distinctive brand identities. The research delves into the significance of trademarks in enhancing consumer trust, fostering brand loyalty, and ensuring market competitiveness for home industry processed food products. It investigates the potential economic impact of trademark infringement and counterfeiting, emphasizing the need for legal frameworks and enforcement mechanisms to safeguard the intellectual property of these small-scale producers. Additionally, the paper discusses the role of trademarks in facilitating market access, both domestically and internationally, by analyzing case studies and industry examples. It explores the correlation between a strong trademark strategy and increased market share, ultimately illustrating how trademarks can serve as powerful tools for differentiation and value creation in a crowded marketplace. Furthermore, the study addresses the challenges that home industry processed food producers may face in the trademark registration process, such as financial constraints and lack of awareness. It offers practical insights and recommendations to empower producers in overcoming these obstacles and establishing a robust trademark strategy. In conclusion, this paper advocates for the urgent adoption and prioritization of trademark strategies by home industry processed food producers. By doing so, these producers can not only protect their intellectual property but also thrive in an increasingly competitive global food market, ensuring the longevity and success of their businesses.